Some Relations between Certain Complex Equations and Nonnormalized Meromorphic Functions - Hüseyin Irmak (Journal of Mathematics)
The purpose of this investigation is first to reveal some relations between certain complex (differential) equations and nonnormalized meromorphic functions and then to point some of their useful consequences out.